Sosialisai Pentingnya Psikologi dalam Dunia Pendidikan di Era Gen-Z SD Negeri 065012 Medan Tuntugan - Regina Sipayung; Patri Janson Silaban; Angela Mericci Alpa Manurung; Rina Wati Lumban Gaol; Betty Agatha Sihombing; Valentina Purba; Hanna Cintia Damanik (Universitas Maritim AMNI Semarang, 2024)
The aim of this research is to find out how psychology influences education in the digital era. Where in the Gen-Z era there is a lot of technology that influences the way of learning and teaching in the educational sphere, one of which is in elementary schools. Psychological education is described as learning about the science of the soul which is based on the literal meaning of the soul to study individual behavior with the aim of finding various facts, generalizations and psychological theories related to education obtained through certain scientific methods. Psychology has several branches of development in children, especially Gen-Z children, namely the sensory engine phase and the intuitive phase. The results of this research show that psychological education in the Gen-Z era is very influential in the world of education, especially in the field of child psychology. The positive impact given to psychological education from childhood can make it easier for children to remember and interact with those closest to them and those around them, so that children can easily find information about learning and can facilitate communication with friends in the Gen-Z era.